2023
DOI: 10.3389/fnut.2023.1097562
|View full text |Cite
|
Sign up to set email alerts
|

Status of nutrition labeling knowledge, attitude, and practice (KAP) of residents in the community and structural equation modeling analysis

Abstract: ObjectiveUnhealthy foods were a major contributor to the occurrence of chronic non-communicable diseases. The promotion of nutrition labeling in the community can effectively help residents to choose healthy foods, which plays an important role in the prevention of chronic diseases. However, the public awareness of this measure is not clear. Our study used a structural equation model based on the KAP theory to analyze the interaction mechanisms among knowledge, attitude, and practice and aimed to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…However, this study only analyzed a short period (2014–2017) that did not include the pandemic period. In addition, studies conducted in China investigating the current food labeling knowledge, attitude, and practice 27 only conducted a survey in a single city with a small sample size (n = 636) and cross-sectional design, and were unable to demonstrate any trend changes. A study conducted in the USA analyzed the food labeling usage of participants with chronic diseases 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this study only analyzed a short period (2014–2017) that did not include the pandemic period. In addition, studies conducted in China investigating the current food labeling knowledge, attitude, and practice 27 only conducted a survey in a single city with a small sample size (n = 636) and cross-sectional design, and were unable to demonstrate any trend changes. A study conducted in the USA analyzed the food labeling usage of participants with chronic diseases 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the situation of healthy diet practices among middle-aged and older adults in southwestern China remains pessimistic. A cross-sectional study showed that although most residents had a positive attitude toward nutrition labeling, the awareness rate of nutrition labeling was only 32.7%, and the utilization rate was 38.5% [ 37 ]. Therefore, further strengthening healthy diet education for middle-aged and older adults, improving their awareness of and attention to healthy diets, and promoting the development of healthy diet habits are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…There were likely several other environmental and social factors that should have been considered in this study. However, previous studies demonstrated that the KAP theory could effectively explain behaviors such as influenza vaccine uptake among healthcare workers (R 2 = 0.69) [ 29 ] and nutrition labeling among residents (R 2 = 0.545) [ 31 ]. The disparity in results could be attributed to the dietary behavior being a relatively ingrained habit formed over a long period, influenced by various social, cultural, environmental, financial, and traditional factors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%